2018
DOI: 10.3926/jotse.338
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence Zambian higher education lecturer’s attitude towards integrating ICTs in teaching and research

Abstract: This paper investigates factors that influence Zambian higher education lecturer’s attitude towards integrating ICTs in research and teaching. To determine these factors, we used online administered survey with a total of 163 respondents from public and private higher education institutions in Zambia. Quantitative data analysis based on descriptive and inferential statistics was used in this study. Inferential analysis was employed to investigate the relationships among variables using Pearson correlation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The concentrate likewise demonstrated that the impact of expertise and involvement with the globalized therapeutic framework on the reception of cloud structure has interceded through the effect of handiness and convenience. This recommends being open to a noteworthy level of involvement and more propelled elements of the globalized therapeutic framework will be both happy utilizing it for learning and see the advantages it offers in supporting their field of restorative calling by ICT aptitude (Kunda et al, 2018). It was found that with open skillful fundamental media clients will probably receive medicinal awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrate likewise demonstrated that the impact of expertise and involvement with the globalized therapeutic framework on the reception of cloud structure has interceded through the effect of handiness and convenience. This recommends being open to a noteworthy level of involvement and more propelled elements of the globalized therapeutic framework will be both happy utilizing it for learning and see the advantages it offers in supporting their field of restorative calling by ICT aptitude (Kunda et al, 2018). It was found that with open skillful fundamental media clients will probably receive medicinal awareness.…”
Section: Discussionmentioning
confidence: 99%
“…While this could easily be done, the COVID-19 context which prompted institutional closures called for rethinking of the ways in which ICT hardware could be provided to students while they studied at home. Similarly, Kunda et al (2018) conclude that lack of adequate internet bandwidth, hardware (in terms of computers for both lecturers and students), and appropriate ICT infrastructure are the major barriers to assimilating ICTs in research and teaching in Zambian Higher Education. These challenges were also revealed in a…”
Section: Effects Of the Covid-19 Pandemic On Frs Studentsmentioning
confidence: 99%
“…Information and Communication (ICT) infrastructure investment in emerging countries still lags behind. Kunda et al (2019) gathered evidence from both public and private higher education institutions in Zambia to investigate factors that impact Zambian lecturers' attitudes about incorporating ICTs in research and teaching activities. They found a positive correlation between the important factors that influence lecturers to assimilate ICTs in an academic environment.…”
Section: Information Systems In Higher Education Institutionsmentioning
confidence: 99%